O ye gentlemen : Arabic studies on science and literary culture in honour of Remke Kruk - Hogendijk, J. P.; Kruk, Remke.; Vrolijk, Arnoud. (Islamic philosophy, theology, and science ;, 2007)
O ye Gentlemen explores two vital strands in Arabic culture: the Greek tradition in science and philosophy and the literary tradition. They are permanent and, though drawing on Islam as a dominant religion, they are by no means dependent on it. That the strands freely interweave within the broader scope of Schrifttum is shown by more than thirty essays on subjects as varied as the social organisation of bees, spontaneous generation in the Shiʿite tradition, astronomy in the Arabian nights, the benefits of sex, precious stones in a literary text, the virtue of women in Judaeo-Arabic stories, animals in Middle Eastern music and the transmission of Arabic science and philosophy to the medieval West.